Real-life effectiveness and safety of baricitinib in 17 Japanese patients with alopecia areata: a 60-week single center study - Akihiko Uchiyama; Takeshi Araki; Keiji Kosaka; Sei-Ichiro Motegi (Journal of Cutaneous Immunology and Allergy)
Alopecia areata (AA) is a chronic immune-mediated skin disorder characterized by non-scarring hair loss. Although clinical trials have shown the effectiveness and safety of baricitinib, there are limited reports that have shown real-world evidence of baricitinib in patients with AA. Herein, we present the real-world data of 17 Japanese adult patients with AA treated with baricitinib at Gunma University Hospital, Japan, for 60 weeks. All patients received 4 mg of baricitinib daily without interruption. The SALT20 achievement was 29.4% (5/17) at week 24, 52.9% (9/17) at week 36, 58.9% (11/17) at week 48, and 64.7% (11/17) at week 60. Patients were categorized as early responders (n = 1), gradual responders (n = 8), late responders (n = 3), and non-responders (n = 5). Exacerbations of alopecia occurred in only one patient. Eleven patients experienced improvement in scalp hair loss at week 12, leading to a significant reduction in the AA-IGA score. At week 24, improvements in eyebrows and eyelashes were noted in 12 and 11 patients, respectively, with significant reductions in their ClinRO scores. The duration of the current episode of AA exceeding 4 years significantly reduced the SALT20 achievement rate (p < 0.027). Common adverse effects included acne (n = 4, 23.5%) and mildly decreased renal function (n = 2, 11.7%). In conclusion, our findings indicate that baricitinib has significant potential for improving intractable severe AA.